Bowel Cleansing Quality in Morning Versus Evening Preparation Regimens for colonoscopy; a Prospective Study - --------- ---------- (مجله كليه طب الكندي, 2012)
Background :Evening preparation for colonoscopy is often unsatisfactory and inconvenient. This study was performed to compare the efficacy of bowel preparation at two different timings: night before and morning of endoscopy and to compare the cecal intubation rate and disturbance of sleep hours between these two groups. Methods: In this prospective randomized endoscopist- blinded trial, 150 patients were enrolled between March 2010 and August 2011. Patients aged between 18 to 80 years needing colonoscopy were included. Patients with prior bowel surgery, suspected bowel obstruction or those who didn't completely fulfill the preparation instructions were excluded. Patients received polyethyelen glycol electrolyte preparation in a morning and evening regimen. Bowel cleansing was scored using the Ottawa Bowel Preparation Quality Scale. Loss of sleep and cecal intubation rate was evaluated. Results: Seventy five patients received morning regimen and 75 patients received evening regimen. There was significant difference in total scores of bowel preparation for the two groups favoring the morning group (ρ < 0.0001) . Bowel cleansing for right and mid colon were significantly better in the morning group (ρ < 0.001), while the difference for the left colon was not significant. The cecal intubation rate was comparable for both groups ( ρ NS).Sleep was disturbed in 15 patients in morning group and in 42 patients in evening group (ρ = 0.003). Conclusion: In conclusion, this study suggests that morning preparation provide better quality of bowel preparation for colonoscopy than evening preparation. Right and mid sided colonic preparation is superior in the patients who take the morning preparation than left sided preparation. Evening preparation is associated with a significant sleep disturbance. This would translate to considerable financial losses and patient discomfort.